Biological treatment of contaminated air with toluene in an airlift reactor - Vergara-Fernández, Alberto O.; Quiroz, Erich F.; Aroca, German E.; Alarcón-pulido, Nelson A. (Electronic Journal of Biotechnology, 2008)
In this work the variation in the toluene elimination capacity of an airlift bioreactor as a function of the toluene inlet load, using compost as the support material for the microorganisms was studied. In order to evaluate the flexibility of the reactor under changing toluene load, the toluene biodegradation was measured for flows from 2.4 x 10-2 to 0.132 m3 h-1, and a concentration range from 1.4 to 0.8 g m-3. Results show a 100% removal efficiency (RE) for minor flows, however, for a flow increase of 450% the RE decreased 40%, reflecting the equipments weak flexibility in varying flows. Meanwhile the maximum elimination capacity obtained was 230 g m-3 h-1, for toluene loads of 550 g m-3 h-1, corresponding to a flow of 0.132 m3 h-1. It was found that a average biomass concentration in suspension of 3700 g m-3, reflected EC's of 203 g m-3 h-1.